Is philosophy dispensable? : and other philosophical essays - Rescher, Nicholas (Ontos Verlag, 2007)
During 2005-2006 I continued my longstanding practice of writing occasional studies on philosophical topics, both for formal presentation and for informal discussion with colleagues. While my forays of this kind have usually issued in journal publications, this has not been so in the preset case so that the studies offered here encompass substantially new material. Notwithstanding their thematic variation, they manifest a uniformity of treatment and method in a way that is characteristic of my philosophical modus operandi and inherent is its endeavors to treat classical issues from novel points of view.' Nicholas Rescher.